Delayed anterior segment complications after the treatment of retinopathy of prematurity with laser photocoagulation - Ajjarapu, Aparna; Dumitrescu, Alina (Frontiers in Ophthalmology, 2023)
Purpose: This retrospective cohort study presents a group of patients who underwent laser therapy for retinopathy of prematurity and presented with delayed anterior segment complications. Methods: Charts of infants treated with laser photocoagulation for retinopathy of prematurity at our institution between 1988 and 2020 were reviewed. Data extracted included demographics, treatment and clinical exam findings, visual acuity, surgical procedures, and cycloplegic refraction. Inclusion criteria were documented anterior segment changes during the follow-up period. Exclusion criteria were any prior intraocular surgery or inflammation before signs of anterior segment complications developed. The exposure was laser photocoagulation for retinopathy of prematurity and the main outcomes were anterior segment complications, visual acuity, and cycloplegic refraction. Results: 183 charts were reviewed. 16 eyes of 9 patients (4.4%) met the inclusion criteria. The mean follow-up period after laser treatment was 15.9 (range, 10-26) years. The mean gestational age at birth was 24.6 (range, 23-27) weeks, and the mean age at first clinical documentation of anterior segment complications was 8.7 (range, 1-25) years. Complications included cataract (n=5 patients/8 eyes) and glaucoma (n=3 patients/5 eyes) with the most frequent complication being band keratopathy (n=9 patients/15 eyes). 5 out of 16 eyes underwent surgical procedures due to anterior segment complications. After treatment, visual acuity improved back to baseline in 4/5 of treated eyes and improved but not to baseline in 1/5 of treated eyes. All patients developed progressive high myopia over the follow-up period. Conclusions: Anterior segment complications after laser photocoagulation for retinopathy of prematurity may develop later in life. They affect visual acuity and quality of life and may require treatment.